2017
DOI: 10.1016/j.expneurol.2017.05.005
|View full text |Cite
|
Sign up to set email alerts
|

PPARgamma agonists rescue increased phosphorylation of FGF14 at S226 in the Tg2576 mouse model of Alzheimer's disease

Abstract: Background Cognitive impairment in humans with Alzheimer's disease (AD) and in animal models of Aβ-pathology can be ameliorated by treatments with the nuclear receptor peroxisome proliferator-activated receptor-gamma (PPARγ) agonists, such as rosiglitazone (RSG). Previously, we demonstrated that in the Tg2576 animal model of AD, RSG treatment rescued cognitive deficits and reduced aberrant activity of granule neurons in the dentate gyrus (DG), an area critical for memory formation. Methods We used a combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 111 publications
(236 reference statements)
1
31
0
1
Order By: Relevance
“…FGF14 was identified to be associated with neuronal signaling in mice ( Wang et al, 2002 ). Recent studies on the FGF14 gene focused on neurology in humans and in mice ( Amado et al, 2017 ; Di Re et al, 2017 ; Hsu et al, 2017 ). Interestingly, this gene was also identified to be a candidate for teat number in Duroc pigs ( Tan et al, 2017 ), implying the pleiotropy of FGF14 .…”
Section: Discussionmentioning
confidence: 99%
“…FGF14 was identified to be associated with neuronal signaling in mice ( Wang et al, 2002 ). Recent studies on the FGF14 gene focused on neurology in humans and in mice ( Amado et al, 2017 ; Di Re et al, 2017 ; Hsu et al, 2017 ). Interestingly, this gene was also identified to be a candidate for teat number in Duroc pigs ( Tan et al, 2017 ), implying the pleiotropy of FGF14 .…”
Section: Discussionmentioning
confidence: 99%
“…Figure 5 b showcases the top 10 significant KEGG pathways ( q < 0.05), and some of them are intensively correlated with AD treatment. For instance, PPAR signaling pathway (ko03320) has been demonstrated to increase phosphorylation of fibroblast growth factor 14 in the Tg2576 mouse model of AD [ 53 ]. Furthermore, a recent study shows that bile secretion (ko04976) is associated with “A/T/N”(amyloid, tau, and neurodegeneration) AD biomarkers, providing further support for a role of bile acid pathway in AD pathophysiology [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…FGF14, as a member of the nonsecreted intracellular FGF family, does not function as an FGF ligand 29 . Previous studies on FGF14 mainly focused on its functions in neural cells 30,31 . Interestingly, a recent study revealed that FGF14 is repressed in patients with nasopharyngeal carcinoma, and FGF14 overexpression suppresses cell proliferation 32 .…”
Section: Discussionmentioning
confidence: 99%